Small and medium-sized towns: Situation, development and prospects in different types of areas - Ulrike Grabski-Kieron; Annabelle Boutet (Cities and metropolises in France and Germany, 2022)
The situation, development lines and perspectives of small and medium-sized towns in Germany and France are compared and similarities and differences within the central place systems and the spatial planning of both countries are discussed. With different approaches to definition, these towns have received new attention in both countries in recent years, albeit with different focal points. The discussion covers the positions and lines of development of these towns in the respective central place systems; the perspectives of their future development regarding the strengthening of central place functions, their attractiveness as residential and economic locations, and contexts of rural regional development and services of general interest. In addition, aspects of research on small and medium-sized towns as well as approaches to spatial policy in both countries are addressed.
urn:nbn:de:0156-1119053; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Central place system; regional planning; regional and urban policy; demographic change; growth and shrinkage; urban-rural relationship; development of rural regions